MDM-KTV: A Conceptual Framework for Multi-Data-Models for Operational, Analytic, Semantic and Linked Data based Data Organization - Martins, Marcelle Batista; Lino, Natasha Correia Queiroz (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2012: Proceedings of the 18th Brazilian Symposium on Multimedia and the Web, 2012)
For developing applications and services in the Knowledge TV platform there is a need in structuring, organising and standardising data according to consolidating academic and industry models, however inserted in the context of interactive Digital TV (iDTV). This work presents research carried on the implementation of the Conceptual Framework MDM-KTV, which means Multi Data Models KTV, considering operational, analytical, semantic and Linked Data based data, in the context of the Knowledge TV project.